2009
DOI: 10.1121/1.3095803
|View full text |Cite
|
Sign up to set email alerts
|

Results of the National Institute for Occupational Safety and Health—U.S. Environmental Protection Agency Interlaboratory Comparison of American National Standards Institute S12.6-1997 Methods A and B

Abstract: The National Institute for Occupational Safety and Health and the Environmental Protection Agency sponsored the completion of an interlaboratory study to compare two fitting protocols specified by ANSI S12.6-1997 (R2002) [(2002). American National Standard Methods for the Measuring Real-Ear Attenuation of Hearing Protectors, American National Standards Institute, New York]. Six hearing protection devices (two earmuffs, foam, premolded, custom-molded earplugs, and canal-caps) were tested in six laboratories usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…[13] Training in the use of hearing protection is crucial to attaining a performance level that approximates what the manufacturer publishes. In two interlaboratory studies using inexperienced subjects, [14,15] a 10-20 dB improvement was observed when the experimenter provided fitting instructions. Joseph et al [16] demonstrated for naïve subjects an improvement in the NRR (subject fit) of 15 dB following individual training and 11 dB following training in small groups.…”
Section: Introductionmentioning
confidence: 91%
“…[13] Training in the use of hearing protection is crucial to attaining a performance level that approximates what the manufacturer publishes. In two interlaboratory studies using inexperienced subjects, [14,15] a 10-20 dB improvement was observed when the experimenter provided fitting instructions. Joseph et al [16] demonstrated for naïve subjects an improvement in the NRR (subject fit) of 15 dB following individual training and 11 dB following training in small groups.…”
Section: Introductionmentioning
confidence: 91%
“…Although the current study did not evaluate a formable earplug, unpublished impulse data collected by NIOSH at the US Army Aeromedical Research Laboratory at Fort Rucker indicated that the IPIL increased with the insertion depth. In general, the insertion depth is a critical factor for achieving an adequate amount of protection when exposed to continuous noise (Murphy et al, 2009;Murphy et al, 2011); therefore, insertion depth should be critical to providing protection from impulse noise.…”
Section: Discussion Acoustic Test Fixture Ear Canal Designmentioning
confidence: 99%
“…These values correspond to an average of the insertion length values measured on each subject by Nélisse et al [18,19] during the experimental procedure. As already done in other studies [16,17,15], test subjects attenuations which can be classified as ''poor fit'' (IL values less than 10 dB at frequencies 6500 Hz) are discarded in the analysis. Indeed, a ''poor fit'' is obviously too far from the model hypotheses.…”
Section: Presence Of Leakagesmentioning
confidence: 99%
“…A similar range of attenuation about 25 dB has been found by Brueck [7] for insertion loss (IL) measured on 12 subjects wearing various EPs, including the Classic EP. Murphy et al [17] have reported range of attenuations even larger, about 35 dB for the Classic EP and about 40 dB for the CMEP (24 adult subjects tested in 6 different laboratories). In a recent study [18,19], investigated the relationships between REAT, IL, and noise reduction (NR) measured on 29 subjects wearing various hearing protectors.…”
Section: Introductionmentioning
confidence: 95%